La lectura con el apoyo familiar en época del COVID 19 en los niños y niñas de séptimo año en la Escuela de Educación Básica “Nudo del Azuay” parroquia Achupallas del cantón Alausí, provincia de Chimborazo, periodo agosto-enero 2020”. - Dominguez Orozco, Carina Elizabeth (2021)
This project entitled "READING WITH FAMILY SUPPORT IN THE TIME OF COVID 19 IN SEVENTH YEAR BOYS AND GIRLS AT THE BASIC EDUCATION SCHOOL" NUDO DEL AZUAY "PARISH ACHUPALLAS DEL CANTÓN ALAUSÍ, PROVINCE OF CHIMBORAZOS, PROVINCE OF CHIMBORAZO 2020" , is determined that it contributes to improving the quality of reading with the support of family members, I want to make known to society the impact that family support has when students read. To carry out this project, the institution provided us with the list of students, as well as authorization to enter the classrooms and carry out the respective surveys, for which the authorities were optimistic and believed that it was appropriate to do this project because there is a large number of relatives in this sector who cannot read which leads to the neglect of the students. By developing this project the students have benefited. This topic has not been done before in the institution, which is of the utmost importance that we focus on the effects of not knowing how to read and not having the support of family members on the students' learning process. For its verification and verification of the research work, surveys were carried out with students, parents and teacher tutor of the seventh year of this educational community, in order to verify the effects produced by not knowing how to read and not having the support of families What's more, the results are not so flattering to say the least. This information will be stored in the library of the State University of Bolívar, so that it can be acquired by members of the institution. To carry out this project we have applied field research since it collects the necessary data to solve the problem. The data collected were obtained by different techniques such as interviews and surveys. A documentary research is also applied since it focuses on a qualitative research technique that is responsible for collecting and selecting information through the reading of documents, books, magazines, recordings, films, newspapers, bibliographies, etc.